Impact of Corpus Luteum Morphology and Progesterone Levels on Pregnancy Outcomes in Embryo Transferred Cows - Akshada Dushyant, Bhujbal; Vitthalarao Ingawale, Maheshkumar; Subhash Patil, Manoj; Ganesh Deshmukh, Shyam; Hemednrakumar Pawshe, Chaitanya; Suresh Ingole, Ranjit; Pralhad Awandkar, Sudhakar (The Indian Journal of Animal Reproduction, 2026)
The corpus luteum size, shape, and echotexture were assessed by transrectal ultrasonography on day seven after synchro nized estrus in twenty recipient cows. The compact corpus luteum was observed in 13 (65%) cows, while the vacuolated corpus luteum was observed in 7 (35%) cows. The pregnancy rate with compact and vacuolated corpus luteum was 7.69 and 57.14 %, respectively, and was found statistically significant at (p